The Effect of Brand Image, Packaging, Advertising and Product Quality on Purchasing Decisions - Farah, Ismi Addini; Mansur, Amin; Lovita, Erna (SAN Scientific, 2024)
This research aims to determine the influence of Brand Image, Packaging, Advertising and Product Quality on Purchase Decisions for Bear Brand Milk Products in Kemayoran. Data was collected using a questionnaire. The data analysis method used is multiple linear regression analysis. The results of the research show that Brand Image has a partially positive and significant effect on purchasing decisions, packaging has a partially positive and significant effect on purchasing decisions, Advertising has a partially positive and significant effect on purchasing decisions, Product Quality has an effect partially positive and significant on purchasing decisions Brand Image, Packaging, Advertising and Product Quality simultaneously have a positive and significant effect on purchasing decisions. This paper contributes by exploring the relationship between the variables Debt-to-Equity Ratio, Earnings Per Share, and Price Earnings Ratio to the stock price, and this study provides an in-depth analysis of how the three financial indicators affect the company's stock price fluctuations. The managerial implications of these findings indicate that companies must focus on strengthening brand image, innovation in packaging design, strategy effective advertising, and continuously maintaining and improving product quality to encourage positive purchasing decisions and create sustainable competitive advantages.